2017 annual report : Saint Lucia: IICA’s contribution to the development of agriculture and rural communities - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The IICA Delegation in Saint Lucia continued to improve on existing mechanisms for delivering technical cooperation services as the vehicles for supporting partners and stakeholders in realizing shared agricultural development objectives of improving agriculture’s capacity to mitigate and adapt to climate change and make better use of natural resources; improving the productivity and competitiveness of the agriculture sector; strengthening agriculture’s contribution to the development of rural areas and the well-being of the rural population; and improving agriculture’s contribution to food security.